Mindfulness training improves relaxation and attention in elite shooting athletes - A single-case study - Bu, D.; Dong Liu, J.; Zhang, C.; Si, G.; Chung, P. (International Journal of Sport Psychology, 2019)
Objective: The current study aimed to examine the effectiveness of a sportspecific mindfulness training program, named, Mindfulness- Acceptance- Insight- Commitment (MAIC) for improving mindfulness, acceptance, training and competition satisfaction, the abilities of relaxation and attention of Chinese elite shooting athletes. Methods: A single-case study research design was adopted. Five elite shooting athletes took part in a mindfulness training intervention, which aimed to enhance their capacity for mindfulness, experiential acceptance, relaxation and attention. The method of the percentage of data points exceeding the median of the baseline phase approach (PEM) was used to calculate the effect sizes for the intervention. Results: Findings of the current study demonstrated a medium to large effects of MAIC training on the increase of mindfulness, relaxation and attention. In the first phase of the intervention, large effects were also revealed for four participants on experiential acceptance, except one athlete. In the second phase of the intervention, medium to large effects for all the participants on experiential acceptance were observed. In addition, in the first phase of the intervention, medium to large effects were found for all of the participants on training and competition satisfaction. In the second phase of the intervention, large effects were also showed for four participants on training and competition satisfaction, except one athlete. Conclusion: It can be viewed that MAIC was effective in improving the levels of mindfulness, attention, and relaxation of elite Chinese shooting athletes. Future studies are suggested to adopt more robust designs such as the randomized control trial designs to further examine the effectiveness of the mindfulness training on elite athletes.